Cloning and expression of Epstein-Barr viral antigens in Escherichia coli : purification of recombinant EBV antigens for diagnostic application - Fones-Tan, Angela. (2009)
One of the factors associated with the etiology of nasopharyngeal carcinoma (NPC) is the Epstein-Barr virus (EBV). Ever since IgA antibodies towards the viral capsid antigen (VCA) and early antigen (EA) showed a high correlation with this disease, indirect immunofluorescence assays (IFAs) to detect these antibodies have conventionally been used to diagnose for NPC. However, this test needs skill to interpret and is not suitable for large-scale screening of populations. ELISA tests are, in contrast, easily automated, quick to perform, and does not involve much skill. However, this test has a high sensitivity which could easily lead to false positivity. Therefore, to maintain specificity, individual EBV antigens have to be purified and coated on the microtitre plates.